PENGARUH REWARD, IKLIM KERJA DAN BUDAYA KERJA TERHADAP MOTIVASI KERJA DAN KINERJA KARYAWAN PT. SAWIT GRAHA MANUNGGAL – TAMIANG INDAH ESTATE KABUPATEN BARITO TIMUR PROVINSI KALIMANTAN TENGAH: ABSTRACT - Karo, Toleransi karo karo (JURNAL KINDAI, 2023)
ABSTRACT Abstract: Toleransi Karo Karo, Effect of Reward, Work Climate on Work Motivation and Employee Performance of PT. Sawit Graha Manunggal – Tamiang Indah Estate, East Barito Regency, South Kalimantan Province, Main Advisor: Ujianto, Assistant Advisor: Dahliana Iskandar This study aims to examine the Effect of Reward, Work Climate on Work Motivation and Employees of PT. Sawit Graha Manunggal – Tamiang Indah Estate, East Barito Regency, South Kalimantan Province. The population in this study were 100 harvest employees of PT. Sawit Graha Manunggal, data were taken from questionnaires distributed to respondents. Data were analyzed using AMOS. The results of this study are Reward has a significant positive effect on work motivation, Work climate has a significant positive effect on work motivation, work culture has a significant positive effect on work motivation, Reward has a significant positive effect on employee performance, Work climate has a significant positive effect on employee performance, Work culture has an effect significant positive effect on employee performance, work motivation has a significant positive effect on employee performance, work motivation does not mediate the effect of rewards on employee performance, work motivation does not mediate the effect of work climate on employee performance, work motivation mediates the effect of work culture on employee performance at PT. Sawit Graha Manunggal – Tamiang Indah Estate Keywords: Reward, Work Climate, Work Motivation, Employee Performance